Adsorption of Mercury Using Different Types of Activated Bentonite: A Study of Sorption, Kinetics, and Isotherm Models - Muhammad Naswir; Jalius Jalius; Desfaur Natalia; Susila Arita; Yudha Gusti Wibowo (Jurnal Rekayasa Kimia & Lingkungan, 2021)
Mercury is a hazardous element because of its toxicity and harmful effects on human health. Various traditional and low-cost methods have been developed to remove mercury from wastewater. This study used local raw material as an alternative adsorbent to treat mercury-contaminated wastewater. Activated bentonite was prepared using different chemical activators (H3PO4, HCl, and ZnCl2) in various concentrations. Then, it was dried at 200°C for an hour. The materials were characterized by SEM-EDS. Its percent removal and isotherm models were analyzed. In this study, the most effective activator was H3PO4 and the experimental data matched the Freundlich model.